EFFECT OF UNIONIZATION ON EMPLOYEES’ PERFORMANCE IN FAMILY OWNED BUSINESSES IN KENYA. A CASE STUDY OF STEEL STRUCTURES LIMITED, NAIROBI. - WOIYE, MARTHA WAUSI (KABARAK UNIVERSITY, 2016)
This study attempted to establish the effect of unionization on employees’ performance in family owned businesses in Kenya. The need to manage employee performance every day is the key to an effective performance management system. The researcher specifically sought to establish the effect of union mediated in compensation on performance of employees in family owned businesses; to determine the effect of union mediated motivation on performance of employees in family owned businesses; to examine the effect of union mediated equal treatment practices on performance of employees in family owned businesses; and to compare aggregate employee performance of unionized employees to nonunionized employees in family owned businesses. The research adopted a descriptive research design. The research study was carried out at Steel Structures Ltd. The study population comprised a total of 614 employees from various functions in SSL. Stratified random sampling technique was used to draw a sample size of 307 respondents. This study used descriptive statistics using statistical measures such as frequency and percentages. In using inferential statistics, the data was analyzed using correlation, which was vital in making sense of the data. Further regression analysis was used to test the relationships between variables. The analyzed data was presented in the form of tables and figures according to the research questions. The regression model further revealed that there was a significant relationship between union mediated motivation and employee performance (p=0.003); there was a significant relationship between Union mediated compensation and employee performance (p=0.012); there was a significant relationship between Union mediated equal treatment and employee performance (p=0.001). The study concluded that unionization aids in achieving better decisions in organization through the existence of trade unions and that existence of trade unions in organizations means that employees through their representatives are involved in many decisions that take place in the organization.
FULL TEXT
Keywords: Trade unions, Employee Performance, Motivation, Compensation, Equal treatment, unionized employees, non unionized employees.